On Materials Imitating Materials: Exploring Historical Decorated Papers - Rusteikaitė, Ieva (Semiotika, 2023)
Crossing the boundaries of any one discipline, the article provides an overview of research into historical decorated paper conducted by the author over the last several years. Examples of this seemingly very specific, ephemeral material, considered as an imitation of other materials, applied in bindings of printed books and manuscripts during the 18th and 19th centuries, are presented as anonymous artifacts of the past, strikingly characterised by their own materiality and thus involving also the researcher’s senses. Besides a historical overview of the main techniques of paper decoration in Europe, the place of this applied decorative element in the three-dimensional structure of the handmade book is also explored. The second part of the paper addresses the relevant problem of ornament as a plastic discourse, which has so far received less attention in semiotic research. Through a closer analysis of a several samples of decorated paper, questions about the semantic structure of the ornament and its effects are raised. Finally, when placed in the context of certain habits, needs and interests of eighteenth-century European society, decorated paper and its ornamental language emerge as a multilayered object with a culturally defined meaning.
Keywords: decorated paper; ornament; decorative arts; book history; plastic semiotics